Monitoring of colloidal fouling and its associated metastability using ultrasonic time domain reflectometry - Sim, S. T. V. (2013)
Ultrasonic Time Domain Reflectometry (UTDR) is used to monitor the deposition and physicochemical nature of colloidal silica fouling on a polyethersulfone ultrafiltration membrane under crossflow and constant flux conditions. The fouling can be characterized by four stages based on the rate of increase of the transmembrane pressure (TMP): (1) an initial rapid increasing rate due to concentration polarization; (2) a slow constant rate; (3) a nonconstant increasing rate associated with metastability of the colloidal silica; (4) a constant rapid rate associated with the foulant layer having a constant thickness. The destabilization of the colloidal particles in the foulant layer during stage 3 is associated with an increase in the UTDR peak amplitude. During stage 4 the foulant layer thickness reaches a plateau value that decreases with increasing crossflow velocity. The rheological behavior of the foulant layer is described by the Bingham plastic model for which the yield stress can be obtained from the UTDR data. When membrane cleaning is done by switching from a fouling to a non-fouling feed solution, marked decreases in both the foulant layer thickness and TMP are observed. However, a residual tightly bound foulant layer remains on the membrane whose thickness, determined by UTDR, corroborates well with off-line scanning electron microscopy analysis.